Flood Prediction Based on Hydrological and Topographic Conditions Using Hec HMS 4.5 and Hec Ras 5. 0. 3 In The Toli - Toli Indonesia - Wijaya, Riki Chandra; Lasminto, Umboro (Jurnal Teknik Sipil, 2023)
Abstract Floods in the Toli-toli area often occur due to the continued reduction in infiltration land. Flood events from year to year have a bigger impact and cause a lot of losses. The impact of this flood needs to be analyzed and its magnitude predicted so that the potential for flooding can be estimated. Flood handling can be addressed early on so that when a flood the losses are not so great. Flood prediction can be done by hydrological analysis using HEC HMS 4.5 and continued hydraulics using HEC RAS ​​5.0.3. Based on the incidence of rain over the last 10 years, it is known that the return period of rain in the Toli-toli area varies from a period of 2 years, 5 years, 10 years, and 15 years. Based on the calculation results, it is known that the flood in the Toli-toli area in the 2-year return period has a depth of 0.66 meters with a flood inundation area as shown in Figure 7 of this article. In overcoming this flood, efforts should be made to handle it with several alternatives such as increasing infiltration land, normalizing rivers, and so on. Keyword: Flood prediction, Toli-toli, hydrological, topographic. Abstrak Banjir di wilayah Toli-toli sering terjadi akibat terus berkurangnya lahan resapan. Peristiwa banjir dari tahun ke tahun memberikan dampak yang lebih besar dan menimbulkan banyak kerugian. Dampak banjir ini perlu dianalisis dan diprediksi besarannya sehingga potensi banjir dapat diperkirakan. Penanganan banjir dapat diatasi sejak dini sehingga ketika terjadi banjir kerugian yang ditimbulkan tidak begitu besar. Prediksi banjir dapat dilakukan dengan analisis hidrologi menggunakan HEC HMS 4.5 dan dilanjutkan hidrolika menggunakan HEC RAS 5.0.3. Berdasarkan kejadian hujan selama 10 tahun terakhir, diketahui periode ulang hujan di wilayah Toli-toli bervariasi mulai dari periode 2 tahun, 5 tahun, 10 tahun, dan 15 tahun. Berdasarkan hasil perhitungan diketahui banjir di wilayah Toli-toli periode ulang 2 tahun mempunyai kedalaman 0,66 meter dengan luas genangan banjir seperti terlihat pada Gambar 7 artikel ini. Dalam mengatasi banjir ini perlu dilakukan upaya penanganan dengan beberapa alternatif seperti memperbanyak lahan resapan, normalisasi sungai, dan lain sebagainya. Kata Kunci: Prediksi banjir, Toli-toli, hidrologi, topografi